2021
DOI: 10.1186/s12889-021-10821-w
|View full text |Cite
|
Sign up to set email alerts
|

Return to work a bumpy road: a qualitative study on experiences of work ability and work situation in individuals with chronic whiplash-associated disorders

Abstract: Background Work resumption is a big challenge in the rehabilitation process for individuals with whiplash-associated disorders (WAD). To better meet the needs of individuals with WAD in their return to work process, more knowledge on their experiences and perspectives is needed. The aim of this study was to explore the experiences of work ability and the work situation of individuals who participated in a neck-specific exercise programme for chronic WAD. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In the present study, virtually the same neck-specific exercise programme was used as in the study by Treleaven et al 33 , but with two additional ventral neck muscle endurance exercises included, which seems to have been successful not only to improve ventral neck muscle endurance (unpublished data), but also to reduce postural sway double stance. Although the effectiveness on postural sway after a neck-specific exercise programme had to be investigated in RCTs, the results of the present study are promising as chronic WAD grades 2 and 3 have been reported to be disabling conditions influencing the whole of life 1 , 3 , 4 , 7 , and to be rather resistant to treatment 1 , 56 58 . Despite no significant differences between the healthy group and the WAD group in single leg stance eyes open, the WAD group improved after intervention, confirming existing knowledge in healthy individuals that sensorimotor disturbance and muscle fatigue are of importance for balance 59 and may be improved after an exercise programme including these elements.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In the present study, virtually the same neck-specific exercise programme was used as in the study by Treleaven et al 33 , but with two additional ventral neck muscle endurance exercises included, which seems to have been successful not only to improve ventral neck muscle endurance (unpublished data), but also to reduce postural sway double stance. Although the effectiveness on postural sway after a neck-specific exercise programme had to be investigated in RCTs, the results of the present study are promising as chronic WAD grades 2 and 3 have been reported to be disabling conditions influencing the whole of life 1 , 3 , 4 , 7 , and to be rather resistant to treatment 1 , 56 58 . Despite no significant differences between the healthy group and the WAD group in single leg stance eyes open, the WAD group improved after intervention, confirming existing knowledge in healthy individuals that sensorimotor disturbance and muscle fatigue are of importance for balance 59 and may be improved after an exercise programme including these elements.…”
Section: Discussionmentioning
confidence: 72%
“…Whiplash-associated disorders (WAD) is a disabling condition 1 after an indirect neck trauma, a whiplash injury, often in connection with a car accident 2 . About half of those with WAD will experience chronic (≥ 6 months) pain and disability 3 , 4 , influencing their health, work and daily life 4 7 .…”
Section: Introductionmentioning
confidence: 99%
“…At the short-term follow-up after surgery, it is important to identify individuals who require further or extended interventions to gain and promote work ability [ 40 ]. A qualitative study on experiences with work ability in chronic WAD grade II and III showed that neck-specific exercise, information about the condition, and practical and emotional support from stakeholders need to be strengthened for increased work ability [ 41 ]. In a review of 18 qualitative studies [ 42 ], moderate evidence was found for collaboration between stakeholders; support from family, friends, colleagues, workplace settings, and health care personnel; and workplace adjustments and self-management strategies for return to work in individuals with musculoskeletal pain.…”
Section: Discussionmentioning
confidence: 99%
“…The WAI is a reliable and valid selfreport scale scored from 7 to 49, with higher scores indicating higher work ability [17]. Scores can be presented as mean values or categorized into four levels when used as an outcome measure: poor , moderate (28)(29)(30)(31)(32)(33)(34)(35)(36), good (37)(38)(39)(40)(41)(42)(43), and excellent (44-49) [18,19].…”
Section: Main Outcome Measurementioning
confidence: 99%
“…Patient satisfaction with the exercises, information, tests, and their total experience with the interventions were measured post intervention. Qualitative interviews were conducted with a proportion of patients after the study [ 31 ], and patients have been involved in the further development of the internet-based program.…”
Section: Methodsmentioning
confidence: 99%